Prices vs. quantities and the intertemporal dynamics of the climate rent - Matthias Kalkuhl; Ottmar Edenhofer (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper provides a formal survey of price and quantity instruments for mitigating global warming. We explicitly consider policies' impact on the incentives of resource owners who maximize their profits intertemporally. We focus on the informational and commitment requirements of the regulator. Furthermore, we study the interplay between (private) resource extraction rent and (public) climate rent and ask how property and management of the climate rent can be assigned between regulator and resource sector. There are only two instruments that unburden the regulator from the complex intertemporal management of the climate rent and associated commitment problems: in the cost-benefit world, we derive a stock-dependent tax rule; in the cost-effective (carbon budget) world, only an emissions trading scheme with free banking and borrowing can shift intertemporal timing decisions completely to the market.
Keywords: Q32; Q38; Q54; Q58; H23; 330; resource extraction; climate rent; intertemporal policy instruments; prices vs. quantities; Hotelling; Klimaschutz; Policy-Mix; Rohstoffwirtschaft; Hotelling-Regel; Rententheorie; Wohlfahrtseffekt; Theorie